(untitled) (Journal of Atomic and Molecular Sciences, 2012)
First-principles investigation on the inelastic electron tunneling spectra of bi-oligophenyleneethynylenes (OPEs)- monothiol molecular junctions is performed. It is demonstrated that the inelastic electron tunneling spectra are very sensitive to the deviation, stagger or separation of the two molecules in the bimolecular junctions. To some extent, the spectra of bimolecular junctions can present similar characteristics as a single OPE-monothiol molecular junction, which reflects the neglectable interaction between two molecules. When the overlap between the two molecules is relatively strong, out of plane vibration modes are active in the spectra and provide more intermolecular tunneling paths for electrons.